Resource recycling and their management under integrated farming system for lowlands of Bihar lowlands of Bihar - KUMAR, SANJEEV; SINGH, S S; MEENA, M K; SHIVANI, SHIVANI; DEY, A (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted at main farm of ICAR Research Complex for Eastern Region, Patna during 2007–10 to study resource recycling from different IFS models and to identify a suitable combination of components for maximum returns and employment generation under lowland situation of Bihar. Different combination of crop, animals, fishes and birds were examined in form of seven integrated farming systems (IFS) models. Among different IFS models crop + fish + duck + goat emerged as the best integrated farming system in terms of productivity, sustainability index (0.80%), net return (` 1 59 485/year) and employment generation (752 man-days/year) apart from addition of appreciable quantity of N, P2O5 and K2O into the system in form of recycled animal and plant wastes. Crop + fish +duck + goat and crop + fish + cattle integration recorded nearly equal amount of rice- grain-equivalent yield. (21.20 and 21.18 tonnes/ha, respectively) but in terms of economics crop + fish +duck + goat supersedes by ` 30 870. The waste material/by products of crops and animals were recycled and used as inputs for other components of integrated farming system. Crop + fish + cattle model added higher quantity of N P and K overall other models.